2018
DOI: 10.4103/sajc.sajc_37_18
|View full text |Cite
|
Sign up to set email alerts
|

Geographical pattern of carcinoma gallbladder in Bihar and its association with river Ganges and arsenic levels: Retrospective individual consecutive patient data from Regional Cancer Centre

Abstract: Background:Indo-Gangetic basin is known to have higher incidence of gallbladder cancer. Proximity to River Ganga and high heavy metal in soil exposure have been postulated as risk factors.Aim:This study aims to evaluate the geographical pattern of gallbladder cancer from consecutive patient database enrolled in hospital-based cancer registry (HBCR).Objectives:To evaluate demographic profile and districtwise/zonewise dispersion of gallbladder cancer cases registered in HBCR from year 2014 to 2016. To evaluate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…It has also been reported that regions with higher arsenic content (>0.05mg/dl) in the soil had 1.45 higher odds of reporting GB cancer. [17] In our study majority of cases (66.34%) were from Gangetic basin districts in comparison to the control group (40%). Gangetic belt emerged as an independent significant factor with an odd's ratio of 2.83.…”
Section: Association Between Dietary Factors and Addiction History To...mentioning
confidence: 45%
“…It has also been reported that regions with higher arsenic content (>0.05mg/dl) in the soil had 1.45 higher odds of reporting GB cancer. [17] In our study majority of cases (66.34%) were from Gangetic basin districts in comparison to the control group (40%). Gangetic belt emerged as an independent significant factor with an odd's ratio of 2.83.…”
Section: Association Between Dietary Factors and Addiction History To...mentioning
confidence: 45%
“…The exact cause of which is still unknown but hypothesis including continuous arsenic exposure and proximity of river Ganga is postulated. [10] Equally alarming is the rising incidence of head-and-neck cancer in Bihar despite ban on tobacco-related products by government. [11]…”
Section: Discussionmentioning
confidence: 99%
“…It's peculiar geographic distribution in our country with incidence rates in North India being ten times higher than South India, has been explained by the increasing industrial pollution of the Ganga and its tributaries. This has lead to exposure of the population residing in these river basins to heavy metals, pesticides, fertilizers and industrial effluents, all carcinogens implicated in causation of GBC [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%